2020
DOI: 10.1021/acsabm.9b01189
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed microRNA Detection Using Metal–Organic Framework for Signal Output

Abstract: A specificity fluorescence platform for probing of sequence-specific miRNA using fluorophore labeled DNA and metal–organic frameworks (MOFs) is developed. Ni-IRMOF-74-II can quench the fluorescence of four fluorescent dyes labeled in the single strand oligodeoxynucleotides (ssODNs), and fluorescence recovers in the presence of their target miRNA and can be detected in their corresponding channels. Furthermore, recovered fluorescence intensity has a linear relationship with the concentration of the target miRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…UIO-66-NH 2 has various unique properties, such as flexible porosity and intrinsic fluorescence quenching which are the reasons for its superior use in biosensors compared to other conventional nanostructures. 34–36 Previously, NMOF has been applied for successful deliver of fluorouracil (5-FU) in HePG-2 cells for fluorescence imaging and cancer therapy. 47 Also, Wu and et al studied a fluorophore-labeled probes that are firmly conjugated with an NMOF as a fluorescence quencher to detect miR-21 in the breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…UIO-66-NH 2 has various unique properties, such as flexible porosity and intrinsic fluorescence quenching which are the reasons for its superior use in biosensors compared to other conventional nanostructures. 34–36 Previously, NMOF has been applied for successful deliver of fluorouracil (5-FU) in HePG-2 cells for fluorescence imaging and cancer therapy. 47 Also, Wu and et al studied a fluorophore-labeled probes that are firmly conjugated with an NMOF as a fluorescence quencher to detect miR-21 in the breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…UIO-66-NH 2 has various unique properties, such as exible porosity and intrinsic uorescence quenching which are the reasons for its superior use in biosensors compared to other conventional nanostructures. [34][35][36] Fig. 6 The fluorescence images of PC3 and A549 cells after treating with FAM-Probe21-NMOF-FA or FAM-Probe21-NMOF complex for 4 h. Previously, NMOF has been applied for successful deliver of uorouracil (5-FU) in HePG-2 cells for uorescence imaging and cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has demonstrated that small, noncoding microRNAs (miRNAs) may play a significant role in the development of diseases such as cancer [ 1 ]. Studies have indicated that both increases and decreases in the activity of miRNAs can lead to the formation of cancer through various pathways [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…This class of compounds is exceptional with respect to high porosity, structural tunability, large internal surface area, and excellent thermal stability. The pore size, shape, and surface area of the MOFs can be tuned according to requirements with proper choices of organic linkers, metal ions, and reaction conditions. MOFs have promising applications in the field of ion exchange, gas adsorption, storage of small molecules, gas separation, heterogeneous catalysis, luminescence, and magnetism. Recently, MOFs have been extensively used for sensing various biomolecules such as antibodies and nucleic acids. Due to their construction, composition, and large internal surface area, MOFs can act as reservoir for antimicrobial agents. This property makes MOFs a new class of high-performance material having potential biotechnological application. …”
Section: Introductionmentioning
confidence: 99%